Breast cancer research and the European Union Clinical Trials Directive - Williams, Norman (BioMed Central, 2004)
Running clinical trials in the commercial sector has always been associated with a certain amount of bureaucracy due to the stringent requirements needed to bring a new drug onto the market. Noncommercial trials have largely been performed outside these requirements. New legislation brought about as a result of the implementation of the European Union Clinical Trials Directive will change this two-tiered approach by harmonizing regulations in all member states. Those who run noncommercial clinical trials will have to find cost-effective ways of dealing with this legislation if such work is to continue in Europe.